Policy controversies and political blame games - Hinterleitner, Markus, 1987- (Cambridge : Cambridge University Press, 2020)
In modern, policy-heavy democracies, blame games about policy controversies are commonplace. Despite their ubiquity, blame games are notoriously difficult to study. This book elevates them to the place they deserve in the study of politics and public policy. Blame games are microcosms of conflictual politics that yield unique insights into democracies under pressure. Based on an original framework and the comparison of fifteen blame games in the UK, Germany, Switzerland, and the US, it exposes the institutionalized forms of conflict management that democracies have developed to manage policy controversies. Whether failed infrastructure projects, food scandals, security issues, or flawed policy reforms, democracies manage policy controversies in an idiosyncratic manner. This book is addressed not only to researchers and students interested in political conflict in the fields of political science, public policy, public administration, and political communication, but to everyone concerned about the functioning of democracy in more conflictual times. This title is also available as Open Access on Cambridge Core.
How political systems manage their policy controversies -- Blame games in the political sphere -- Blame games in the UK -- Blame games in Germany -- Blame games in Switzerland -- Mapping the influence of institutional factors -- Mapping the influence of issue characteristics -- A typological theory of blame games and their consequences -- Blame games and their implications for politics and democracy under pressure.
Title from publisher's bibliographic system (viewed on 29 Oct 2020).
Keywords: Political culture -- Western countries -- Case studies; Comparative government; Democracy -- Western countries -- Case studies; Opposition (Political science) -- Western countries -- Case studies; Political planning -- Western countries -- Case studies; Crisis management in government -- Western countries -- Case studies; Blame -- Political aspects -- Western countries -- Case studies; Government accountability -- Western countries -- Case studies; Western countries -- Politics and government